Tingkat pengetahuan dan sikap mahasiswa Fakultas Farmasi Universitas Muhammadiyah Surakarta tentang beyond use date obat - Alinda, Oevita Nur; Karuniawati, Hidayah (Journal of Pharmaceutical and Sciences, 2024)
Beyond Use Date (BUD) is the expiry time of a drug after it is opened from its primary packaging. The aim is to determine the level of knowledge and attitudes regarding BUD, to analyze whether there are differences between sociodemographics and BUD knowledge and attitudes, as well as whether there is a relationship between knowledge and attitudes of students in the Muhammadiyah University of Surakarta Pharmacy study program regarding BUD. This research is descriptive analytical research with observational methods. The data collection method was cross-sectional. Analysis (using Mann-Whitney and Kurskall-Wallis analysis) was carried out to assess differences in mean knowledge and attitude scores. Linear regression analysis was carried out to identify factors related to knowledge and attitudes about BUD. Spearman Rank analysis was used to test the correlation between knowledge and attitudes. The research results showed that respondents had a sufficient level of knowledge at 53,0% and attitude about BUD were classified as good at 68,8%. Statistical analysis shows that knowledge and attitudes about BUD are significantly related to age and generation (p<0,001). The research results also stated that men, respondents aged 17 and 18 years and the class of 2023 had a lower understanding of knowledges and attitude about BUD. Apart from that, there is a correlation between knowledge and attitude (p=0,000).